Improving clinical practice through simulation training on intellectual disabilities: a longitudinal study. Issue 5 (30th June 2020) - Iannelli, Hannah; Tooley, Camilla; Billon, Grégoire; Cross, Sean; Pathan, James; Attoe, Chris
Abstract : Purpose: Individuals health with intellectual disabilities (ID) experience comorbid physical and mental health needs and have poorer outcomes resulting in early mortality. Currently, many training provisions based on ID exist; however, limited research supports their effectiveness. High-fidelity simulation is an innovative training mechanism with promising preliminary results. This study aims to evaluate the longitudinal impact of simulation training on clinical practice in ID. Design/methodology/approach: A mixed-method approach was used in this study. A one-day simulation course using actors who had ID was delivered to 39 health-care professionals from across London hospitals. Nine semi-structured interviews were conducted 12–18 months post training. Findings: High-fidelity simulation training is an effective training modality, which has a sustainable impact on participants, their clinical practice and patients. Core features of the training including debriefing, the use and type of actors, scenario design and the facilitators are crucial learning mechanisms which impacts learning outcomes and changes to behaviour in clinical practice and settings. Originality/value: To the best of the authors' knowledge, this study is the first to longitudinally evaluate high-fidelity simulation training designed to improve the physical and mental health needs of those with ID. The research begins to bridge an important gap in the current literature, with a need for more research.